Functional Outcome of Tip Apex Distance in Predicting Implant Failure in Intertrochanteric Fracture Femur Treated with Dynamic Hip Screw - Hafiz Umair Hussain, Ahmad Jamal, Manzoor Hussain, Muhammad Ishfaq, Muhammad Mahmood Ahmad, Muhammad Kamran Siddiqui (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the importance of tip apex distance in implant failure in intertrochanteric fracture femur treated with Dynamic hip screw, so that optimum tip apex distance should maintain to decrease the implant failure in intertrochanteric fracture femur treated with DHS. Study Design: It was a descriptive cross sectional study. Study Setting and Duration: Patients were selected from orthopedic unit of Nishtar Hospital, Multan, from July 2020 to June 2021. Methodology: All patients meeting the inclusion criteria who presented with a femur fracture were included in the analysis. SPSS version 24.0 was used to analyse the data. Quantitative data analysis was done using means and standard deviations like age and tip apex distance. Categorical variables like gender, functional outcome and implant failure was calculated and presented as frequency and percentage. Results: A total of 81 patients with mean age of male patients were 38.51 and SD was 11.79, similarly in female patients mean age was 41.87 and SD 11.60. Mean tip apex distance in male was 16.08 and SD 8.49, in female mean tip apex distance was 15.40 and SD 9.368. Tip Apex distance was ≤ 25 cm in 61 (75.3%) patients and >25 cm in 12 (24.7%) patients. As concern to the outcome variable (implant failure) 12 (14.8%) patients were having implant failure and 69 (85.2%) patients were having successful outcomes. Practical implication: The use of Dynamic Hip Screw in Intertrochanteric Fracture Femur treated would show improved clinical results and fewer hardware failures Conclusion: Tip Apex distance is a valuable measurement in dynamic hip screw fixation of Intertrochanteric fracture femur. Keywords: Fracture, Femur, Tip Apex Distance, Dynamic Hip Screw, Implant Failure, Orthopedic